Analisis Pengenalan Literasi Digital pada Anak di Lingkungan Keluarga - Arifin, Zainal; Asoka Niscahya Alam Mayang (STIT Sirojul Falah Bogor, 2024)
Human interaction patterns with digital media are becoming more intense as a result of digital disruption. Digital media can be beneficial, but it can also be detrimental. Therefore, digital literacy skills are needed to help people use digital media correctly, especially children. This can start from the family environment as the smallest organization closest to the child. This research aims to analyze the introduction of digital literacy to children in the family environment. This research was conducted by conducting a systematic literature review using a qualitative approach. Data collection techniques by examining Google Scholar-based journal article sources that are relevant to the research study. After collecting and obtaining data that is in accordance with the research study, the data is then analyzed using the content analysis method. The results of research on introducing digital literacy to children in the family environment can be divided into 4 parts, including 1) children are good imitators, 2) parents' digital literacy skills, 3) guidance and control, 4) developing digital literacy habits.